Hybridisation experiments between freshwater prawns Macrobrachium amazonicum and M. pantanalense (Decapoda: Palaemonidae), and the effects of geographical isolation - Nogueira, Caio Santos [UNESP]; Pantaleão, João Alberto Farinelli; Costa, Rogerio Caetano [UNESP] (CSIRO Publishing, 2021)
The freshwater prawns Macrobrachium amazonicum and M. pantanalense are phylogenetically closely related. The present study analysed the occurrence of copulation between these two species. Specimens of M. amazonicum were collected from the Tietê River in Cambaratiba (SP), whereas M. pantanalense specimens were collected from the Lagoa Baiázinha, in Miranda (MS). Six different experimental groups were used, MA♂ × MP♀, MA♀ × MP♂ (interspecifc), MA♂ × MA♀, MP♂ × MP♀ (intraspecific), MA♀ and MP♀ (individualised; MA = M. amazonicum and MP = M. pantanalense). The incubation times of the ovigerous females were monitored in all experiments. Some females from all experimental groups were randomly selected and had their oocytes photographed to verify the occurrence of embryonic development. No larvae hatched in the interspecific experimental groups, whereas, in intraspecific groups, almost all experiments (95%) presented larval hatching. The incubation period differed significantly (P < 0.001) between the intraspecific groups and all the other experimental groups, but not between each other (P > 0.05). The interspecific and individualised groups showed no significant (P > 0.05) difference between them. In addition, oocytes from the interspecific experimental groups did not present characteristics of embryonic development. Our results suggest that M. pantanalense and M. amazonicum populations do not copulate, which corroborates the proposal of recent speciation.
Keywords: genetic distance; intraspecific recognition; pantanal; reproductive barrier; sexual behavior